Cerebral Ischemia due to Aortic Arch Thrombosis Secondary to Iron Deficiency Anemia - Taha Nisar; Rajanigandhi Hanumanthu (Case Reports in Neurological Medicine)
Thrombocytosis, hypercoagulable state, and hypoxia secondary to anemia are some of the mechanisms that are thought to cause strokes in patients with iron deficiency anemia (IDA). Several cases of middle-aged females with IDA who had embolic strokes due to aortic arch thrombosis have been reported. Majority of the cases were treated with anticoagulation. We report another case of embolic strokes in a patient with IDA treated with anticoagulation and iron replacement without recurrence of further episodes. We concluded that embolic phenomenon in middle-aged females with IDA warrants transesophageal echocardiogram with an evaluation of aortic arch.